RISIKO KERUSAKAN HATI KARENA PARASETAMOL DALAM DOSIS TERAPI - Cicih Komariah (Jurnal Ilmu Kesehatan Masyarakat, 2007)
Paracetamol , a safe and effective drug that is commonly used and in many countries and is available as over the counter (OTC) preparation and hence dispensed by the pharmacist without a prescription. Paracetamol is widely used for the management of common cold, dysmennorhea, head ache, fever and pain. Because of its safety profile and cost, it is one of the preferred drugs and is used as a household remedy. This condition develop to the indicipline and misuse of paracetamol consumption. The studies that have been conducted by pharmacologist have proofen that the large dose, not regimen dose, of  paracetamol is safe to be consumed. They do not realize that paracetamol is a deadly painkiller, even at the recommended dose. Paracetamol poisoning is associated with many complications and may affect and hepatotoxicity is the major complication leading to death. The lack of knowledge on the part of patient on the side effects makes it dangerous for them to consume the drug. Without explicit warning on the packs of these drugs, it is putting the patient under severe risk pertaining to toxicity, particular the liver. This article try to describe that paracetamol consumption could intervere body health particularly the liver. Some case reports about liver damage after paracetamol ingestion also included to show that people must be aware  about the drug consumption even it is looks like safe and no harm for human body like paracetamol. It is ironic if the medicine we take to make us better just make us more suffer with other health problem which could be deadly. Keywords : paracetamol, recommended dose, liver damage